Freezing Colloids: Observations, Principles, Control, and Use Applications in Materials Science, Life Science, Earth Science, Food Science, and Engineering - Deville, Sylvain (Engineering Materials and Processes,, 2017)
This book presents a comprehensive overview of the freezing of colloidal suspensions and explores cutting-edge research in the field. It is the first book to deal with this phenomenon from a multidisciplinary perspective, and examines the various occurrences, their technological uses, the fundamental phenomena, and the different modeling approaches. Its chapters integrate input from fields as diverse as materials science, physics, biology, mathematics, geophysics, and food science, and therefore provide an excellent point of departure for anyone interested in the topic. The main content is supplemented by a wealth of figures and illustrations to elucidate the concepts presented, and includes a final chapter providing advice for those starting out in the field. As such, the book provides an invaluable resource for materials scientists, physicists, biologists, and mathematicians, and will also benefit food engineers, civil engineers, and materials processing professionals.